Validade do índice cardiotorácico em radiografias de tórax como método diagnóstico de cardiomegalias - Maronezi, Luis Felipe Chaga (2020)
Objectives: To evaluate the applicability of cardiothoracic ratio (CTR), in posteroanterior (PA) chest radiographs, in detection of cardiomegaly, determining its diagnostic parameters according to diferente cutoff points. Methods: Cross-sectional and diagnostic validy study with 1.544 patients aged 18 or over, with chest X-ray and echocardiography exams, executed in a maximum interval of one month, between 2015 and 2018. CTR was mensured by the ratio between transverse cardiac diameter (TCD) and transverse toracic diameter (TTD), and the parameters of left ventricular mass index (LVMI) and left ventricular diastolic diameter (LVDD), in two-dimensional echocardiography, were used as gold standard. The diagnostic parameters were evaluated according to sex and different cutoff points. Results: There was 1.544 patients, with a predominance of men (55,4%), aged 63,1±15,0 years and with CTR of 49,7±7,2%. Accuracy, sensitivity, specificity, positive and negative predictive values and likelihood ratio (LR+ and LR-) for the CTR>50% were, respectively, 69,7%, 69,7%, 69,7%, 57%, 80%, 2,299 and 0,435, changing according to sex. Greater accuracy was found at the cutoff point 55% for the general population (70,6%), 50% for men (70,9%) and 60% for women (69%). The area under the curve for the CTR variable was 0,752. Conclusions: CTR is a good method of cardiomegaly screening, but not diagnostic confirmation, with parameters that change according to sex and cutoff points. Advances in knowledge: The cutoff point used for the diagnosis of cardiomegalies on the radiograph can be decisive for a better accuracy of the method.